HLA Polymorphisms and Haplotype Diversity in Transylvania, Romania - Mihaela L. Vică; Horea V. Matei; Cosmina I. Bondor; Gheorghe Z. Nicula; Costel V. Siserman; Luminița Loga; Lucia Dican (Journal of Immunology Research)
Transylvania is a historical region in the northwestern part of Romanian with a rather heterogeneous population. Our study is the first to determine human leukocyte antigen (HLA) profiles in a large population sample from this region and to compare them with other European population groups. HLA genes were examined in 2,794 individuals using the Single Specific Primer-Polymerase Chain Reaction (SSP-PCR) and Polymerase Chain Reaction Sequence-Specific Oligonucleotide (PCR-SSO) methods. All samples were tested for the HLA-A locus, 2,773 for HLA-B, 1,847 for HLA-C, and 2,719 for HLA-DRB1 loci. HLA gene frequency data from several European population groups (as presented in studies involving more than 1,000 individuals) served as reference in comparison with the local sample. The distribution of HLA genes in the studied population group was heterogeneous, as the Hardy-Weinberg equilibrium was statistically significant (P value < 0.01). The most common genes found in our sample group were A∗02 (0.27%), B∗35 (0.14%), C∗07 (0.25%), and DRB1∗11 (0.19%). The most common haplotype was A∗01~B∗08~C∗07~DRB1∗03 (1.26% in 1,770 individuals with complete data). This analysis confirmed the known heterogeneity of the Transylvanian population. The study indicates that the European population groups located in close vicinity (those from Serbia, Hungary, Wallachia, and Croatia) are genetically closest to the Transylvanian population.